Biochemical and microbiological characteristics of in situ biofilm formed on materials containing fluoride or amorphous calcium phosphate - Ferreira, Lilian [UNESP]; Pedrini, Denise [UNESP]; Okamoto, Ana Cláudia [UNESP]; Jardim Jr., Elerson Gaetti [UNESP]; Henriques, Tássia Araújo [UNESP]; Cannon, Mark; Delbem, Alberto Carlos Botazzo [UNESP] (My University, 2013)
Purpose: To evaluate the biochemical and microbiological characteristics of in situ biofilm formed on materials that release fluoride (F-) or calcium (Ca++) and phosphate (Pi). Methods: This study comprised an in situ and in vitro experiment, utilizing three materials [Auralay XF and Fuji IX GP, containing fluoride, and Aegis containing amorphous calcium phosphate (ACP)] and bovine dental enamel slabs. For the in situ: 10 volunteers wore palatal devices, each containing four material specimens or enamel slabs that were treated with 20% sucrose solution. The biofilm had pH measurements on Day 7 and the composition was analyzed on Day 8 by assessing the following: F', Ca++, Pi and insoluble extracellular polysaccharides (EPS) concentrations, and then identification of the microbiota. For the in vitro: materials/enamel were subjected to a 7-day pH-cycling regimen to determine F, Ca++ and Pi release. Results: The biofilm formed on F-releasing materials was richer in F, Ca++ and Pi and had lower mutans streptococci counts than enamel biofilm. The biofilm on the ACP-containing material exhibited similar Ca++ and Pi concentrations to biofilm on F-releasing materials. The materials showed buffering action compared with enamel. Biochemical and microbiological characteristics showed a less cariogenic biofilm on materials containing fluoride or amorphous calcium phosphate.